Sistem Informasi Penjualan Makanan Berbasis Web Menggunakan Metode User Centered Design - Yuvita Ratih Dewi; Ahmad Aditia Prayoga; Nurmansyah (CV. Shofanah Media Berkah, 2023)
This research proposes the development of a web-based food sales information system using the User-Centered Design (UCD) method at Cafe Markas Pancong UJ. The UCD method is employed to prioritize user needs in the development of this system. The system includes features such as online ordering, menu management, order tracking, and customer data management. The implementation of this system is expected to enhance operational efficiency, expand marketing reach, and improve customer satisfaction. The results of this research indicate that the development of a web-based information system using the UCD method offers an effective solution for small and medium-sized enterprises.